Determinants of Solar Photovoltaic Adoption among Mobile Micro Enterprises: A Technology Acceptance Model Approach - Iriandy; Ahmad Wahidiyat Haedar; Nurul Aliah; Ayu Saputri Bahar (Information Technology Education Journal, 2025)
This study investigates the determinants influencing the adoption of solar photovoltaic (PV) systems among mobile micro-enterprises in Makassar, Indonesia. Drawing upon the Technology Acceptance Model (TAM) extended with two contextual constructs Energy Needs and Ease & Support the research employs a quantitative cross-sectional design involving 30 mobile coffee vendors. Reliability and regression analyses confirm the model’s robustness, indicating that Perceived Usefulness, Technology Acceptance, and Energy Needs significantly predict the intention to adopt PV systems, while Ease & Support shows no significant effect. The study extends the application of TAM to the informal micro-enterprise context, which has rarely been explored in renewable energy adoption research. Findings highlight that perceived economic benefits and energy necessity outweigh technical convenience in shaping adoption behavior. This suggests that micro-entrepreneurs’ motivation is primarily driven by practicality and efficiency rather than ease of use. The results provide policy insights for promoting inclusive green transitions through targeted micro-financing, technical training, and supportive urban regulations for small mobile vendors. Overall, this pilot investigation offers a validated framework for future empirical studies on renewable energy adoption within developing-country micro-enterprise sectors.